Studies on low-skilled migrant workers in Malaysia in 2000-2018: a literature review - Awang Ideris Awang Daud; Dzurizah Ibrahim (Fakulti Kemanusiaan, Seni dan Warisan, UMS, 2022)
Malaysia is a popular destination for low-skilled migrant workers primarily from developing and less developed countries. Their huge presence in the country has consequences for the economy and society which have sparked interest among scholars in studying multitude of low-skilled migrant workers issues. Despite the volume of studies on low-skilled migrant workers, which cover a broad range of issues, little is known about the trend and direction of this stream of research. This paper aims to identify and highlight the main research traditions and scopes of the low-skilled migrant workers studies in Malaysia by reviewing 35 articles published between 2000 and 2018. Although there are no peculiar patterns observed for the 19-year period, the increase in interest to write or research on low-skilled migrant workers among scholars is quite evidenced lately. Authors of the papers reviewed generally preferred to use either the terms “migrant workers” or “foreign workers” to refer to the low-skilled non-citizen workers in Malaysia. Almost all studies reviewed were empirical in nature that adopted more of the qualitative rather than quantitative approaches to analyze low-skilled migrant worker issues. Social, behavioral, policy, legal and workers’ rights issues were more dominant as compared to economics and health related issues.